A Study on Factors Influencing the Choice of Motor Insurance Policies among Car Owners in Bangalore (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
A motor insurance policy provides an essential layer of financial security against the risks associated with a motor vehicle, including accidents, theft, natural hazards and liability risks to third parties. As the number of cars on the road has risen, technology has advanced, and the competition among insurance companies has grown, there has been greater interest in the factors that affect customer choice of motor insurance policy. The present study is an attempt to find out the important factors that affect the selection of Motor Insurance policies among vehicle owners in Bangalore. The research design used was a descriptive research design, and the data collected were primary data from 250 car owners who were given a structured questionnaire. A method called Exploratory Factor Analysis (EFA) was used to look for the dimensions that underlie policy choices. The Kaiser-Meyer-Olkin (KMO) index value was 0.894 with a significant Bartlett's Test of Sphericity, thus showing the data to be appropriate for factor analysis. The findings showed that there were five key determinants of policy selection: Service Quality and Claim Settlement, Premium and Cost Considerations, Company Reputation and Trust, Policy Coverage and Benefits, and Digital Convenience. A total of 72.84 per cent of the variance was accounted for by these five factors. Of these, the most significant factors impacting customer decisions were Service Quality and Claim Settlement. The results indicate that policies that boast quick claims settlement, low rates, full coverage, reliable insurance companies, and digital platforms are desirable to customers. The study offers valuable information for insurance companies to define their strategies towards customers and to enhance the attractiveness of their policies in a competitive market.